Recent update on lactic acid bacteria producing riboflavin and folates: application for food fortification and treatment of intestinal inflammation - Levit, Romina (2021)
Lactic acid bacteria (LAB), widely used as starter cultures for the fermentation of a large variety of food, can improve the safety, shelf life, nutritional value and overall quality of the fermented products. In this regard, the selection of strains delivering health-promoting compounds is now the main objective of many researchers. Although most LAB are auxotrophic for several vitamins, it is known that certain strains have the capability to synthesize B-group vitamins. This is an important property since humans cannot synthesize most vitamins, and these could be obtained by consuming LAB fermented foods. This review discusses the use of LAB as an alternative to fortification by the chemical synthesis to increase riboflavin and folate concentrations in food. Moreover, it provides an overview of the recent applications of vitamin-producing LAB with anti-inflammatory/antioxidant activities against gastrointestinal tract inflammation. This review shows the potential uses of riboflavin and folates producing LAB for the biofortification of food, as therapeutics against intestinal pathologies and to complement anti-inflammatory/anti-neoplastic treatments.